Interpretable mapping of fine-grained urban building functions from street-view images using foundation models - Jiaming Sun; Wei Yang; Tingting Xu; Zongshun Tian; Yongchuan Zhang; Mengjia Yin (Computers, Environment and Urban Systems, 2026)

A kidney-targeted MOF nanozyme combats calcium oxalate crystal-induced kidney injury - Xuhong He; Min Zhou; Zhengxin Liang; Shiyi Jin; Kunze Yu; Longxiyu Meng; Zhicong Tan; Jinming Xu; Jiaju Xu; Chongjun Xiang; Jingchao Wei; Wenjun Gao; et al. (Chemical Engineering Journal, 2026)

Thermal-buffering cellulose aerogels with competitive hydrogen bonding: Dual-enthalpy synergy for efficient solar desalination - Mengqi Lu; Shuyue Zhang; Jiangquan Yang; Wei Li; Shuangfei Wang; Shouxin Liu; Jiaming Sun; Shuangxi Nie (Chemical Engineering Journal, 2026)

Machine vision-based impurity content assessment of paddy grains for pre-storage quality monitoring - Liu Yang; Xinfeng Hu; Can Shu; Jiaming Wang; Nianwu Wei; Tianqing Liu; Qian Liu; Menghao Zhao; Zhiwei Liu; Shaoyun Song (Journal of Stored Products Research, 2026)

Potential of individual-scale phenological measurements for improving wood productivity and maintaining genetic diversity in forest management - Haruka Sano; Tai-Shen Chen; Jiaming Yan; Naoko Miura; Minoru Inamori; Wei Guo; Sachiko Isobe; Kazutaka Kusunoki; Hiroyoshi Iwata (Forest Ecology and Management, 2026)

Sex-specific differences in cadmium accumulation and responses in the freshwater snail Cipangopaludina cathayensis - Wei Jinyou; Xiang Shanshan; Yu Jing; Li Linli; Tan Haizhen; Ye Quanqing; Yang Liu; Deng Yufan; Cui Jiaming; Wu Zhengjun; Jiang Jiaoyun (Chemico-Biological Interactions, 2026)

Abscisic acid promotes watercore dissipation by accelerating sorbitol decomposition through the MdNAC25-MdSDH8 module in apple fruit - Yali Li; Hao Wei; Qian Ma; Jiaming Li; Zuanhong Xu; Yamei Ren; Xiaolin Ren; Yuduan Ding (Postharvest Biology and Technology, 2026)

Targeted “ROS storm” in hypoxic periodontitis: A self-enhanced SDT/CDT synergistic platform based on triple-enzymatic Cu-Mo bimetallic nanozyme - Wei Wu; Tong Xu; Kehan Wu; Lilong Yang; Jiaming Wang; Kaidi Liang; Dan Yang; Piaoping Yang; Narisu Hu (Chemical Engineering Journal, 2026)

Explicit wave height prediction model and regularity analysis for floating breakwaters based on deep symbolic regression - Jiaming Jing; Xiaofei Cheng; Haibo Chen; Wei Xie (Frontiers in Marine Science, 2026)
The accurate prediction of wave attenuation across floating breakwaters is essential for coastal structure design and nearshore aquaculture safety. This study employs Physical Symbolic Optimization (PhySO) to model the transmission of significant wave height (H s ) and maximum wave height (H max ) behind a floating breakwater in Lianjiang, Fujian Province. Using in-situ wave data including incident wave height, period, and direction, the dataset is split into 80% training and 20% testing sets, with constraints on expression complexity and physical consistency. Results show that PhySO produces explicit, interpretable formulas with strong generalization ability: the best H max expression achieves accuracy comparable to black-box machine learning models, while H s expressions show slightly lower but still reliable performance. Simple linear scaling expressions exhibit excellent robustness across all wave conditions, and incident wave height is confirmed as the dominant controlling factor. This work demonstrates the value of PhySO in balancing accuracy and physical interpretability, offering a practical and easy-to-use tool for engineering applications.

Gibberellic acid modulated ethylene, ascorbate-glutathione cycle, and fatty acid metabolism to attenuate the browning of watercore apple fruit: Insights from transcriptomic evidence - Yali Li; Hao Wei; Yunya Zhao; Jiaming Li; Zuanhong Xu; Changhao Song; Yamei Ren; Xiaolin Ren; Yuduan Ding (Postharvest Biology and Technology, 2026)

Study on the synergistic melting combustion characteristics of municipal solid waste incineration fly ash and circulating fluidized bed gasification fly ash - Wei Li; Jiaming Chen; Shaobo Yang; Qiangqiang Ren (Fuel, 2026)

Components with potential anti-inflammatory effect from the seeds of Dolichos lablab - Wei Zhang; Yijin Wu; Jiaming Cheng; Jingya Ruan; Yingying Wang; Lequan Yu; Dan Wang; Yi Zhang; Tao Wang (Journal of Natural Medicines, 2026)

Mass and Energy Balance-Oriented Allocation Mechanism for Petrochemical Product Carbon Footprint - Lili Sun; Hongju Chen; Hetian Zhu; Xiaotong Li; Jiaming Gu; Yinghui Han; Guofei Shen; Yunhu Gao; Baojuan Dou; Chong Wei; Qun Shen; Wei Wei (Aerosol Science and Engineering, 2026)

How built environments shape leisure jogging styles: Nonlinear and interactive effects across objective and subjective dimensions - Wei Yang; Mengjia Yin; Longyang Huang; Jiaming Sun; Caixuan Guo; Xin Fan; Jingjing Li (Journal of Transport Geography, 2026)

The E3 ligase RNF5 facilitates viral replication by suppressing innate immune responses in grouper - Yanqi Zhao; Xiaohui Zheng; Siting Wu; Minyao Bi; Jiaming Hu; Shaojie Liu; Jingguang Wei; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Environmental exposure to bisphenol S suppresses white adipocyte beiging and energy expenditure via CYP2E1 in mice - Qi Liu; Yuancheng Shao; Jiaming Xue; Yicheng Jiang; Shuai Chen; Dongmei Wang; Yan Zhou; Jie Zhao; Wei Gao; Liming Tang (Environmental Pollution, 2026)

Research on bearing capacity of laser welding reinforcement of spherical joint region of spatial grid structure - Caibao Liu; Xiongyan Li; Wei Wang; Suduo Xue; Jiaming Yang (Engineering Structures, 2026)

Co-pyrolysis mechanism of 1,1,1,2-tetrafluoroethane and soapstock: ReaxFF molecular dynamic and density functional theory study - Mengna Bai; Erguang Huo; Wei Zhuang; Jiaming Wang (Journal of Environmental Chemical Engineering, 2026)

Biomimetic tactile sensor for dynamic-static perception based on piezoionic and piezoresistive effects - Huanyu Liu; Jiaming Fan; Yongqi Kuang; Jing Xu; Qizhao Liang; Zhimeng Liu; Jun-Wei Zha; Yunhui Wu (Chemical Engineering Journal, 2026)

Targeting argH to attenuate Aeromonas dhakensis virulence: A metabolic checkpoint for biofilm formation and stress adaptation - Xueqian Wang; Chenlu Yang; Xuesong Li; Wei Feng; Jianguo Zhao; Yukun Wu; Shuai Ye; Meng Zhao; Hanzeng Li; Jiaming Ju; Guiying Guo; Lixia Fan; et al. (Veterinary Microbiology, 2025)

Machine learning-driven design for globally optimal performance of flexible pressure sensors - Yuhan Zhao; Zhanfeng Guo; Zetian Zhao; Hengbin Ding; Xiaoshi Li; Yihan Xu; Daixuan Wu; Zhongheng Sun; Yifan Li; Jiaming Li; Ruolan Zhao; Minghao Wang; et al. (Chemical Engineering Journal, 2025)

Torsional Deformation of Existing Tunnels Induced by Obliquely Undercrossing Shield Tunneling - Jiaming Ou; Xiaochun Zhong; Lisu Sun; Wei Wang (Geotechnical and Geological Engineering, 2025)

Research on the dynamic properties of rubber-recycled brick-coarse aggregate concrete through pore structure evolution - Shucheng Yuan; Jiayu Zeng; Jiaming Mai; Siwei Du; Yanjindong Yi; Kunpeng Li; Wei Liang (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

ZnP-H2Im glass for flame retardant wood: In situ vitrification and synergistic mechanisms - Zhipeng Zhang; Jinrong He; Yuzhang Wu; Jiaming Luo; Wei Qu (Chemical Engineering Journal, 2025)

Adipose-derived soluble fractions activated bioink promotes cutaneous repair and regeneration via mobilizing endogenous reparative cells - Wei Zhang; Jiaming Shao; Hanlei Zhou; Min Yang; Chenghao Cai; Fang He; Yiran Wang; Pengqin Xu; Sizhan Xia; Tingting Weng; Jialiang Wang; Ronghua Jin; et al. (Chemical Engineering Journal, 2025)

Integrated multi-omics reveals mechanistic impact of gut microbiota inhibition on lignocellulose biodegradation in Tenebrio molitor - Xinrui Mao; Jiaming Li; Wenbiao Jin; Wei Han (Bioresource Technology, 2025)

Digital simulation of condensation and water loss in ventilated lychee packaging - Jicheng Lin; Xiaodan Zhang; Yihong Jiang; Dongfeng Liu; Wei Cai; Guopeng Lin; Zhiwu Ding; Enli Lü; Jiaming Guo (Biosystems Engineering, 2025)

Optimization of green development for methylene diphenyl diisocyanate industry based on synergistic benefit - Qun Shen; Qianqian Chen; Li Shang; Nannan Sun; Jiaming Gu; Tao Li; Hongbei Wang; Weisheng Yu; Xuehang Song; Wei Wei (Journal of Environmental Chemical Engineering, 2025)

Hydrophilic and lipophilic diblock polymer-based co-delivery nanoplatform for impossible mission: Resistance management toward insecticides via Nrf2-sMaf pathway - Jiajia Zhao; Zeng Wang; Jiaming Yin; Ying Wei; Mingshan Li; Jialin Gou; Meizhen Yin; Jie Shen; Shuo Yan (Chemical Engineering Journal, 2025)

Insight shift from laboratory to industrialization for tail gas-based ethanol production - Jiaming Gu; Danfeng Wang; Qun Shen; Li Shang; Guofei Shen; Nannan Sun; Shuhuan Tong; Wei Chao; Yangyang Guo; Wei Wei (Chemical Engineering Journal, 2025)

Numerical Simulation of an Icebreaker Ramming the Ice Ridge - Wenbo Dong; Jiaming Chen; Yufei Zhang; Shisong Wei; Guangwei He; Fang Li (Journal of Marine Science and Engineering, 2025)
During polar navigation, icebreakers frequently encounter ice ridges, which can significantly reduce navigation efficiency and even pose threats to structural safety. Therefore, studying the ramming of ice ridges by the icebreaker is of great importance. In this study, the ice ridge is decoupled into the consolidated layer and the keel for modeling. The consolidated layer is simplified as layered ice, and an innovative hybrid empirical–numerical method is used to determine the icebreaking loads. For the keel, a failure model is developed using the Mohr–Coulomb criterion in combination with the effective stress principle, accounting for shear failure in porous media and incorporating both cohesion and internal friction angle. The ship is restricted to surge motion only. A comparative analysis with the model test results was conducted to assess the accuracy of the method, with the predicted ice resistance showing deviation of 9.85% in the consolidated ice area and 10.48% in the keel area. Ablation studies were conducted to investigate the effects of different ice ridge shapes, varying retreat distances, and different ship drafts on the performance of ramming the ice ridge. The proposed method can quickly and accurately calculate ice ridge loads and predict their motion responses, providing a suitable tool for on-site rapid navigability assessment and for the design of icebreakers.

Neuroprotective effects of Yangming-Kaixin-Yizhi formula in Alzheimer’s disease: dual regulation of PI3K/Akt and p38 MAPK signaling via network pharmacology and experimental approaches - Jing Lei; Jiaming Li; Wei Wu; Rui Xiong; Yao Liu; Yong Tang (Metabolic Brain Disease, 2025)

Differential impacts of rain event and continuous rainfall on biological phosphorus removal of a full-scale wastewater treatment plant: performance analysis and optimization strategies - Jiaming Hu; Lu-Man Jiang; Lihua Wang; Xinya Ding; Xinhong Han; Yan Zhang; Haijuan Wei; Zhan Qiu; Ying An; Zhen Zhou (Journal of Environmental Management, 2025)

Intumescent flame-retardant wood: In situ polymerization of ionic liquids and its mechanism - Jinrui Jiang; Yuzhang Wu; Jiaming Luo; Wei Qu (Chemical Engineering Journal, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Enhancing the separation of iron and manganese from high-iron rhodochrosite through medium-low temperature calcination and leaching - Jiaming Chen; Jiancheng Shu; Huimin Yang; Sha Zhang; Jun Luo; Jing Wang; Hongyuan Zhao; Zongchen Wei; Yong Yang; Zongyu Deng; Mengjun Chen (Process Safety and Environmental Protection, 2025)

Interface catalysis over AlPO4/Al2O3 with F-Al-O species for resource utilization of hydrofluorocarbon greenhouse gas - Yiwei Sun; Xiaoli Wei; Fangcao Liu; Bing Liu; Jiaming Zhao; Yubao Bi; Wenfeng Han (Journal of Environmental Chemical Engineering, 2025)

Coordinated transcriptional regulation of carbohydrate-related pathways contributes to the difference of starch accumulation between starchy cassava and sugary cassava - Zehong Ding; Lili Fu; Ganlu Chen; Yan Yan; Weiwei Tie; Xianwei Meng; Jinghao Yang; Xianjin Qiu; Jiaming Zhang; Wei Hu (Carbohydrate Polymers, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Enhanced removal of Cr(VI) from aqueous solutions by an electric field and iron–manganese oxalate composites - Shushu Liao; Kaiyuan Liang; Jiancheng Shu; Yunhui Han; Jiaming Chen; Shaoqin Chen; Jun Luo; Shengjie Wang; Mengjun Chen; Hanke Wei; Zongyu Deng (Journal of Environmental Chemical Engineering, 2025)

Anti-PD-L1 blockade facilitates antitumor effects of radiofrequency ablation by improving tumor immune microenvironment in hepatocellular carcinoma - Jiahua Liang; Mingjian Ma; Wei Feng; Qiongcong Xu; Dong Chen; Jiaming Lai; Jiancong Chen (Apoptosis, 2025)

Ecological and Evolutionary Factors Contribute to the Uneven Diversification of Firs in the Northern Hemisphere - Qiaoping Xiang; Jie Yang; David S. Gernandt; Tongxin Ye; Ling Yang; Jiaming Pan; Ruichen Xiang; Cheng Zhao; Koh Nakamura; Xianchun Zhang; Yongbo Liu; Ran Wei (Journal of Biogeography, 2025)
Aim The Northern Hemisphere harbours the greatest diversity of temperate plants on Earth, with East Asia having the highest species richness compared with North America and Europe. When and how this uneven diversification pattern emerged remains unclear. Here, we use a conifer genus that forms extensive forests in the Northern Hemisphere to explore a fundamental question in ecology and evolution: what processes underlie temperate biodiversity through time and space? Location The Northern Hemisphere. Taxon Abies . Methods To reconstruct a well‐supported framework for estimating diversification rate, we performed phylogenetic analyses using concatenation and coalescent methods based on 58 fir taxa and 56 nuclear single‐copy genes. Niche evolution was explored using species occurrence data and environmental factors based on the l1ou model. Multiple regression was carried out to identify correlations between species richness and environmental variables at global and regional scales, to evaluate factors of species diversity preference, and potentially to explain the evolutionary history of firs. Results We identified East Asia as having the highest species diversity and speciation rate. Two clade‐specific niche shifts corresponding with the distribution of firs were detected, one in the Himalaya‐Hengduan Mountains ( c. 12.2 Ma) and the other in the Mexican highlands ( c. 14.3 Ma), but none in the Euro‐Mediterranean region. Fir species richness increased with cool temperatures both globally and regionally. Seasonal precipitation showed significant positive correlation to species richness on a global scale and in North America and the Euro‐Mediterranean region. Soil factors showed significant trends and moderate correlations with species richness in the Himalaya‐Hengduan Mountains and Mexican highlands. Main Conclusions Our results indicate that modern firs prefer cool climates with seasonal rainfall. East Asian firs experienced niche shifts with the Himalayan orogeny in the Middle Miocene. Novel heterogeneous habitats due to changes in topography and the establishment of a monsoon climate, accompanied by niche shift, can account for the high speciation of firs in East Asia. A similar process is found in the Mexican highland firs. In contrast, cold–dry continental climate in North America since the late Paleogene and the lack of seasonal rainfall and relatively stable topography in the Euro‐Mediterranean region are the main limiting factors for fir diversification. Our study rejects the ‘clade age’ hypothesis but supports the hypothesis that niche shift related to high diversification rate triggered by environmental heterogeneity underlies the uneven species diversity of the Northern Hemisphere.

Mechanistic insights into the hydrogel-supported catalyst for superior oxygen evolution performance - Yuxuan Wei; Lingling Xu; Kefan Shi; Hanwen Gong; Jiaming Hu; Xianghao Zhang; Meilan Pan; Edison Huixiang Ang (Chemical Engineering Journal, 2025)

Development of a portable multi-step microfluidic device for point-of-care nucleic acid diagnostics - Lulu Shi; Zirui Pang; Jianghao Yu; Jiaming Zhu; Xiaohong Xie; Shiling Xie; Lichuan Gu; Wei Hu; Hai Xu; Ling Li; Jifang Tao; Mingyu Wang (Analytica Chimica Acta, 2025)

Development of poly(butylene oxalate-co-furanoate) copolymers with enhanced sustainability and hydrolytic degradability - Lizheng Wang; Zhu Tu; Jiaming Liang; Yanyu Wang; Zhiyong Wei (Journal of Hazardous Materials, 2024)

Efficient depolymerization of lactic acid oligomers into lactide with low racemization - Jiaming Yu; Ting Li; Qifeng Wei; Xiulian Ren (Journal of Environmental Chemical Engineering, 2024)

A strategy for treatment of low-grade ore: Efficient separation and purification of iron - Shishun Dong; Ting Li; Jiaming Yu; Qifeng Wei; Xiulian Ren (Process Safety and Environmental Protection, 2024)

Nano ZnO modified amorphous carbon materials enabling long-cycle performance and high-capacity for lithium/sodium-ion batteries - Jiaming Liu; Zhen He; Tongfa Zhao; Yuqian Wei; lingpei Hou; Yunfei Song; Yuxin Wang (Chemical Engineering Journal, 2024)

Corrigendum to “Implanted 3D gelatin microcryogel enables low-dose cell therapy for osteoarthritis by preserving the viability and function of umbilical cord MSCs” [Chem. Eng. J. 416 (2021) 129140] - Xiaoguang Zhang; Shaokai Liu; Zhenxing Wang; Chao Luo; Zhipeng Dai; Jiaming Sun; Yong Liu; Zengwu Shao; Shuhua Yang; Hui Wang; Juan Wang; Wei Chen; et al. (Chemical Engineering Journal, 2024)

Regulatory mechanisms of miR171d–SCL6 module in the rooting process of Acer rubrum L. - Huiju Li; Jiayu Yu; Jiaming Qin; Hewen Zhao; Kezhong Zhang; Wei Ge (Planta, 2024)

Trajectory tracking PID passivity-based control of spacecraft formation flying around Sun-Earth L2 point in the port-Hamiltonian framework - Jiaming Wang; Qingrui Zhou; Wei Zheng; Jingdong Diao (Advances in Space Research, 2024)

Compositions and sources of fluorescent water-soluble and water-insoluble organic aerosols - Hao Ma; Dandan Liu; Junjun Deng; Jiaming Zhao; Qiang Zhang; Zhimin Zhang; Wei Hu; Libin Wu; Pingqing Fu (Science of The Total Environment, 2024)

ILP1 and NTR1 affect the stability of U6 snRNA during spliceosome complex disassembly in Arabidopsis - Jiaming Wu; Wei Chen; Shengchao Ge; Xueliang Liu; Junling Shan; Meishan Zhang; Yuan Su; Yunfeng Liu (Plant Science, 2024)

The resistance to anoikis, mediated by Spp1, and the evasion of immune surveillance facilitate the invasion and metastasis of hepatocellular carcinoma - Zhengwei Zhang; Xiaoning Chen; Yapeng Li; Feng Zhang; Zhen Quan; Zhuo Wang; Yang Yang; Wei Si; Yuting Xiong; Jiaming Ju; Yu Bian; Shibo Sun (Apoptosis, 2024)
Anoikis-Related Genes (ARGs) lead to the organism manifesting resistance to anoikis and are associated with unfavorable prognostic outcomes across various malignancies.Therefore, it is crucial to identify the pivotal target genes related to anoikis in HCC .We found that ARGs were significantly correlated with prognosis and immune responses in HCC. The core gene, SPP1, notably promoted anoikis resistance and metastasis in HCC through both in vivo and in vitro studies. The PI3K-Akt-mTOR pathway played a critical role in anoikis suppression within HCC contexts. Our research unveiled SPP1’s role in enhancing PKCα phosphorylation, which in turn activated the PI3K-Akt-mTOR cascade. Additionally, SPP1 was identified as a key regulator of MDSCs and Tregs migration, directly affecting their immunosuppressive capabilities.These findings indicate that in HCC, SPP1 promoted anoikis resistance and facilitated immune evasion by modulating MDSCs and Tregs. Graphical Abstract

Erratum to: Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Multiple synergistic antibacterial melamine-impregnated paper based on nano Ag-doped ZIF-8 - Jinrong He; Wei Qu; Yun Feng; Jinrui Jiang; Jiaming Luo; Yuzhang Wu; Limin Peng (Chemical Engineering Journal, 2024)

Binary-Network structured PI@SiO2 nanofibrous composite aerogels with temperature invariant superelasticity for thermal insulation - Qicheng Xue; Nanxi Dong; Peiqi Fan; Daolei Lin; Guofeng Tian; Jun Liu; Jiaming Wei; Shengli Qi; Dezhen Wu (Chemical Engineering Journal, 2024)

Poly(butylene oxalate-co-terephthalate): A PBAT-like but rapid hydrolytic degradation plastic - Lizheng Wang; Zhu Tu; Jiaming Liang; Zhiyong Wei (Journal of Hazardous Materials, 2024)

Development of CaCl2·6H2O-mannitol/SiO2 shape-stabilized composite phase change material for the radiant cooling panel system - Jiaming Zhang; Haiwen Li; Yanliang Du; Tao Xu; Ting Zou; Shen Wei; Dongqiao Zhang (Energy and Buildings, 2024)

Cryopreserved leukapheresis material can be transferred from controlled rate freezers to ultracold storage at warmer temperatures without affecting downstream CAR-T cell culture performance and in-vitro functionality - Jiaming Wei; Katherine Chaney; Woo Jin Shim; Heyu Chen; Grace Leonard; Sean O'Brien; Ziyan Liu; Jinlin Jiang; Robert Ulrey (Cryobiology, 2024)

Responses of physiological, microbiome and lipid metabolism to lignocellulose wastes in gut of yellow mealworm (Tenebrio molitor) - Xinrui Mao; Jiaming Li; Enqing Meng; Wenbiao Jin; Wei Han (Bioresource Technology, 2024)

Aggregation, retention and transport of γ-MnO2 nanoparticles in water-saturated porous media: Impact on the immobility of thallium - Jiaming Luo; Dafeng Cai; Lezhang Wei; Hang Shi; Yu Liu; Haiqi Yan; Dinggui Luo; Tangfu Xiao; Xuexia Huang; Qihang Wu (Environmental Pollution, 2024)

Carbon emissions and low-carbon development in Olefin industry - Qun Shen; Jiaming Gu; Li Shang; Shuang Liu; Xuehang Song; Weisheng Yu; Yongping Liu; Nannan Sun; Wei Wei (Environmental Research, 2024)

Weather data-centric prediction of maize non-stressed canopy temperature in semi-arid climates for irrigation management - Hope Njuki Nakabuye; Daran R. Rudnick; Kendall C. DeJonge; Katherine Ascough; Wei-zhen Liang; Tsz Him Lo; Trenton E. Franz; Xin Qiao; Abia Katimbo; Jiaming Duan (Irrigation Science, 2024)

Research on anode pressure control and dynamic performance of proton-exchange membrane fuel cell system for vehicular application - Heng Wei; Changqing Du; Xingyi Li; Chenxu Shi; Jiaming Zhang (Fuel, 2024)

In-situ preparation of N-rich nano-activated carbon on negative-charged montmorillonite with enhanced activation of peroxymonosulfate for antibiotics degradation - Wei Wang; Yan Huang; Jiaming Ni; Weijun Peng; Yijun Cao; Yukun Huang; Guixia Fan; Daoguang Teng; Shaoxian Song (Journal of Environmental Chemical Engineering, 2023)

A novel fish CRADD inhibits Singapore grouper iridovirus (SGIV) infection by mediating apoptosis and modulating SGIV CARD (VP48)-caspase-2 interaction - Xin Zhang; Siting Wu; Zetian Liu; Jiaming Liao; Jingguang Wei; Qiwei Qin (Aquaculture, 2023)

Enhanced recovery of high purity Cu powder from reclaimed copper smelting fly ash by NH3·H2O–NH4Cl slurry electrolysis system - Jiaming Chen; Tianya Lei; Jiancheng Shu; Wenxing Cao; Xiangfei Zeng; Fan Lin; Shushu Liao; Mengjun Chen; Liang Wei; Weiping Huang (Journal of Cleaner Production, 2023)

Role of mining waste trade on green development in China: Policy implications for circular economy - Siming Yu; Xun Wang; Jiaming Liu; Fang Wei (Resources Policy, 2023)

Isolation and identification of a megalocytivirus strain (SKIV-TJ) from cultured spotted knifejaw (Oplegnathus punctatus) in China and its pathogenicity analysis - Jiaming Liao; Shaozhu Kang; Luhao Zhang; Dongzhuo Zhang; Zhuqing Xu; Qiwei Qin; Jingguang Wei (Fish & Shellfish Immunology, 2023)

Experimental study on the characteristics of radiation floor cooling system based on an earth–air heat exchanger - Jiaming Yang; Wei Song; Houan Zhang; Jing Wang; Jiankai Dong (Energy and Buildings, 2023)

Influence of hemin on structure and emulsifying properties of soybean protein isolate - Jiaming Zhang; Yangyang Jia; Wenjin Wu; Yingying Zhang; Ping Chen; Xiaofang Li; Xuetuan Wei; Chunmei Li; Kaikai Li (Food Chemistry, 2023)

The carbon reduction effects of stepped carbon emissions trading and carbon capture and storage on hybrid wind-PV-thermal- storage generation operating systems - Yongmei Wei; Xinyu Wang; Jin Zheng; Yihong Ding; Jiaming He; Jian Han (Environmental Science and Pollution Research, 2023)

The Intensification of Prolonged Cooling Climate-Exacerbated Late Ordovician–Early Silurian Mass Extinction: A Case Study from the Wufeng Formation–Longmaxi Formation in the Sichuan Basin - Zhibo Zhang; Yinghai Guo; Hengye Wei; Chunlin Zeng; Jiaming Zhang; Difei Zhao (Journal of Marine Science and Engineering, 2023)
The Late Ordovician–Early Silurian period was a significant transitional phase in geological history and has garnered global interest. This study focuses on the black shale series of the Wufeng Formation–Longmaxi Formation of the Upper Ordovician–Lower Silurian period in the Sichuan Basin. Based on the logging curves and lithological characteristics of the Yucan-1 Well, 46 black shale samples were collected from the target layer section for clay mineral XRD (46 samples) analysis and whole-rock XRF (14 samples) analysis. The results indicate that three third-order sequences (SQ1, SQ2, and SQ3) are present in the Wufeng Formation–Longmaxi Formation of the Yucan-1 Well, and two subfacies and three microfacies were identified. In conjunction with the characteristics as well as the characteristic parameters of whole-rock oxide and clay mineral content ((I/C), (S + I/S)/(I + C), CIA, CIA-error, CIW, PIA, MAP, and LST), the Wufeng Formation–Longmaxi Formation of the Yucan-1 Well is divided into three intervals. Interval I is the Wufeng Formation. During this interval, weathering intensity, surface temperature, and precipitation gradually decreased, while the climate shifted from warm and humid to cold and dry. This corresponds to two pulse-type biological extinction events and represents an interval of increasing organic carbon burial. Interval II encompasses the bottom-middle part of the Longmaxi Formation. Weathering intensity, surface temperature, and precipitation were characterized by smooth, low values. Subsequently, the climate was predominantly cold and dry. This was the primary interval of organic carbon enrichment. Interval III extends from the upper part to the top of the Longmaxi Formation. Weathering intensity, surface temperature, and precipitation gradually increased. The climate transitioned from cold and dry to warm and humid. Organic carbon burial gradually decreased, while sea levels dropped. This indicates that climate cooling was the primary controlling factor for this biological extinction event. In combination with previous divisions of graptolite zones in the Yucan-1 Well, it is postulated that this biological extinction event may primarily have been pulse extinction. The continuous cooling of the climate in the later period led to the continuous extinction of organisms that survived the disaster. Until approximately 438.76 Ma at the top of the Longmaxi Formation, the climate environment recovered to pre-extinction conditions, with a transition to a warm and humid climate again.

Four new terpenoids and other metabolites with potential anti-complementary activities from the aerial parts of Dracocephalum moldavica (Lamiaceae) - Jiaming Wang; Jinfeng Sun; Long Jin; Yanyan Huang; Mengjie Wang; Mei Jin; Shengbao Diao; Wei Zhou; Gao Li (Natural Product Research, 2023)

Establishment and characterization of a brain tissue cell line from spotted knifejaw ( Oplegnathus punctatus ) and its susceptibility to several fish viruses - Jiaming Liao; Xin Zhang; Shaozhu Kang; Luhao Zhang; Dongzhuo Zhang; Zhuqing Xu; Qiwei Qin; Jingguang Wei (Journal of Fish Diseases, 2023)
Cells are important in the study of virus isolation and identification, viral pathogenic mechanisms and antiviral immunity. The spotted knifejaw ( Oplegnathus punctatus ) is a significant farmed fish in China that has been greatly affected by diseases in recent years. In this study, a new cell line derived from the spotted knifejaw brain (SKB) was established and characterized. SKB cells multiplied well in Leibovitz's L‐15 medium supplemented with 10% fetal bovine serum at 28°C. Chromosome analysis revealed that modal chromosome number was 48 for SKB. SKB cells exhibit susceptibility to several fish viruses, such as a largemouth bass virus, red grouper nervous necrosis virus (RGNNV), infectious spleen and kidney necrosis virus (ISKNV), Singapore grouper iridovirus (SGIV) and spotted knifejaw iridovirus isolate (SKIV‐TJ), as shown by cytopathic effect and increased viral titers. Electron microscopy results showed that the cytoplasm contained a large number of vacuoles, and many virus particles existed at the edge of the vacuoles in RGNNV‐infected cells and numerous viral particles were scattered throughout the cytoplasm in both ISKNV‐ and SKIV‐TJ‐infected cells. These results suggest that SKB is an ideal tool for studying host–virus interactions and potential vaccine development.

Global-aware siamese network for change detection on remote sensing images - Ruiqian Zhang; Hanchao Zhang; Xiaogang Ning; Xiao Huang; Jiaming Wang; Wei Cui (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Depth-dependent drivers of soil aggregate carbon across Tibetan alpine grasslands - Junxiao Pan; Jiawei Shi; Dashuan Tian; Ruiyang Zhang; Yang Li; Yunlong He; Lei Song; Song Wang; Yicheng He; Jiaming Yang; Chunxue Wei; Shuli Niu; et al. (Science of The Total Environment, 2023)

Electron-transfer pathways insights into contaminants oxidized by Cu-OOSO3- intermediate: Effects of oxidation states of Cu and solution pH values - Lele Zhao; Jiaming Zhang; Zhiping Zhang; Yujun Zhu; Yuan Zong; Chengying Bai; Tong Wei; Yueming Ren; Jun Ma (Journal of Hazardous Materials, 2023)

Antibacterial anodic aluminium oxide-copper coatings on aluminium alloys: preparation and long-term antibacterial performance - Jiahuan Chen; Zhen He; Jiaming Liu; Yuxin Wang; Michael Hodgson; Wei Gao (Chemical Engineering Journal, 2023)

Optimization of a compact on-site stormwater runoff treatment system: Process performance and reactor design - Yangjie Qin; Chuanting Zhou; Siqi Yu; Hongjian Pang; Jiaming Guo; Jun Wei; Libing Wang; Yunxin Xing; Ying An; Zhen Zhou (Chemosphere, 2023)

Ancient and modern mitogenomes of red deer reveal its evolutionary history in northern China - Bo Xiao; Tianjiao Wang; Adrian M. Lister; Junxia Yuan; Jiaming Hu; Shiwen Song; Haifeng Lin; Siren Wang; Chunxue Wang; Dong Wei; Xulong Lai; Xiumei Xing; et al. (Quaternary Science Reviews, 2023)

A new monoterpenoid glycoside and a new phenolic glycoside isolated from Dracocephalum moldavica and their anti-complementary activity - Jiaming Wang; Jinfeng Sun; Long Jin; Mengjie Wang; Yanyan Huang; Mei Jin; Wei Zhou; Gao Li (Natural Product Research, 2023)

Excess pore water pressure and seepage in slopes induced by breaking internal solitary waves - Zhuangcai Tian; Lei Jia; Jiaming Xiang; Guotao Yuan; Kun Yang; Jun Wei; Mingwei Zhang; Honglei Shen; Jianhua Yue (Ocean Engineering, 2023)

Microbially driven fate of terrigenous particulate organic matter in oceans - Lianbao Zhang; Mingming Chen; Yue Zheng; Jianning Wang; Xilin Xiao; Xiaowei Chen; Chen Hu; Jiaming Shen; Jihua Liu; Kai Tang; Dapeng Xu; Qiang Shi; et al. (Limnology and Oceanography, 2023)
A long‐standing enigma in oceanography is why terrestrial organic matter is “missing” in the global ocean, despite the considerable discharge into it every year. Although some explanations, such as mineralogical composition, hydrodynamic processes, and priming effect, have been proposed, we hypothesize that the essential mechanism behind the missing organic matter is microbial processing, for which the underlying coupled geochemical, molecular, and genetic evidence is unknown. An ultra‐large‐volume, long‐term river–seawater stratified simulation system was constructed to unravel the microbially driven fate of terrigenous particulate organic matter (POM) in oceans. Analysis of combining the molecular with POM chemical composition data suggests that Bacteroidetes could act as pioneers in the processing of terrigenous POM in oceans, degrading high‐molecular‐weight, high‐carbon compounds such as polysaccharides. Remaining low‐molecular‐weight nitrogenous organic matter is subsequently degraded by Planctomycetes and Proteobacteria. Isotopic signals show that this preferential degradation causes a distinct “aging” effect of POM, and along with nitrification enhanced by remineralization, causes a decrease in the POM C : N ratio. Degradation of terrigenous POM and bacterial biomass biosynthesis leads to positive deviations in δ 15 N and δ 13 C. Relatively refractory hydrocarbons, aromatic compounds, and phenols are accumulated by microbial processes in this system. This study provides mechanistic insights into the missing chemical and isotopic signals and microbially driven fate of terrigenous POM in the ocean, with important implications for how riverine material input affects marine carbon and nitrogen cycling.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Ultrasonic-assisted synthesis of highly stable RuPd bimetallic catalysts supported on MgAl-layered double hydroxide for N-ethylcarbazole hydrogenation - Xiaoran Liu; Jiaming Shi; Xuefeng Bai; Wei Wu (Environmental Science and Pollution Research, 2022)

Tilt deformation and instability of the slope for predicting rainfall-induced landslide - Handong Liu; Jing-jing Liu; Jiaxing Chen; Jiaming Luo; Wei Guo (Arabian Journal of Geosciences, 2022)

NoiD, a DedA membrane protein required for homeostasis maintaining of Rhizobium leguminosarum biovar viciae during symbiosis with Pisum sativum - Xiaofang Li; Jiaming Xu; Yajuan Wei; Zirui Chen (Symbiosis, 2022)

Two new phenolic glycosides with anti-complementary activity from the roots of Sanguisorba officinalis L - Rongshen Wang; Jinfeng Sun; Mei Jin; Chao Ye; Jiaming Wang; Long Jin; Ying Jie Ma; Wei Zhou; Gao Li (Natural Product Research, 2021)

Low-intensity pulsed ultrasound ameliorates angiotensin II-induced cardiac fibrosis by alleviating inflammation via a caveolin-1-dependent pathway - Kun Zhao; Jing Zhang; Tianhua Xu; Chuanxi Yang; Liqing Weng; Tingting Wu; Xiaoguang Wu; Jiaming Miao; Xiasheng Guo; Juan Tu; Dong Zhang; Bin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2021)

Mapping of a major QTL for salinity tolerance at the bud burst stage in rice (Oryza sativa L) using a high-density genetic map - Lei Lei; Zhenghong Han; Bowen Cui; Luomiao Yang; Hualong Liu; Jingguo Wang; Hongwei Zhao; Wei Xin; Xianwei Li; Jiaming Li; Jingnan Cui; Shanbin Xu; et al. (Euphytica, 2021)

Two novel flavonoids from the leaves of Rhododendron dauricum L. with their inhibition of TNF-α production in LPS-induced RAW 264.7 cells - Chao Ye; Mei Jin; Chunshi Jin; Rongshen Wang; Jiaming Wang; Ying Zhang; Sainan Li; Jinfeng Sun; Wei Zhou; Gao Li (Natural Product Research, 2021)

A new pentacyclic triterpenoid from the leaves of Rhododendron dauricum L. with inhibition of NO production in LPS-induced RAW 264.7 cells - Jiaming Wang; Mei Jin; Chunshi Jin; Chao Ye; Yi Zhou; Rongshen Wang; Huanhuan Cui; Wei Zhou; Gao Li (Natural Product Research, 2020)

A new aryldihydronaphthalene-type lignan and other metabolites with potential anti-​inflammatory activities from Corispermum mongolicum Iljin - Yi Zhou; Mei Jin; Chunshi Jin; Chao Ye; Jiaming Wang; Jinfeng Sun; Cheng-Xi Wei; Wei Zhou; Gao Li (Natural Product Research, 2020)

Study of mosaicism of Pyropia yezoensis - Yuan He; Wei Zhou; Jiaming Li; Songdong Shen (Marine Biology Research, 2019)

Synergistic effect of EMS1-shRNA and sorafenib on proliferation, migration, invasion and endocytosis of SMMC-7721 - Jiaming Zhou; Li Chen; Yixin Zhang; Yuanyuan Wu; Guilan Wang; Song He; Zhongying Guo; Yingze Wei (Journal of Molecular Histology, 2014)

Extensive tRNA Gene Changes in Synthetic Brassica napus - Lijuan Wei; Zeshan An; Annaliese S. Mason; Meili Xiao; Ying Guo; Jiaming Yin; Jiana Li; Donghui Fu (Journal of Molecular Evolution, 2014)

Characterization of transcriptional activation and inserted-into-gene preference of various transposable elements in the Brassica species - Caihua Gao; Meili Xiao; Lingyan Jiang; Jiana Li; Jiaming Yin; Xiaodong Ren; Wei Qian; Ortegón Oscar; Donghui Fu; Zhanglin Tang (Molecular Biology Reports, 2012)

AtRabD2b, a Functional Ortholog of the Yeast Ypt1, Controls Various Growth and Developmental Processes in Arabidopsis - Fang Wang; Chao Liu; Chen Wei; Yuhai Cui; Qian Zheng; Jiaming Zhang; Jiangsheng Wu; Kede Liu (Plant Molecular Biology Reporter, 2012)